Управление процессом формирования готовности педагогов ДОО к инновационной деятельности - Muchkaeva E. K. (Preschool education: experience and future development, 2017)
For the modern teacher, it takes a very special team – a team that love their work of teachers-adherents. Teachers need to combine all the best human qualities – high moral and spiritual development, honesty, justice, skill of the teacher, deep understanding, and in addition always be prepared for the changing realities of this world.
Keywords: инновационная деятельность; модель; ФГОС ДО; инновационная педагогика; innovation; innovation pedagogy; Federal state educational standard of preschool education model